Rancang Bangun Aplikasi E-Ticketing Travel Antar Kota Berbasis Android - Ciksadan Ciksadan1; Abdul Rakhman; Indri Maharani Safira (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
The main cause of the decline in the existence of air Cihampelas service is so expensive. So many people are switching using Cihampelas land as Travel between cities for example, as alternative means. This transport is rated more pocket friendly, because the cost offered is more affordable. But the community is still very minimal in the Kokoro which is about the availability of a successful trip. This is due to the provision of tickets that are still conventional. Therefore, by utilizing technology officials in the current communication, the author is interested to create a travel reservation system application that can run in a smartphone. This app will only be devoted to Android-based smartphones. The creation of this app uses Android Studio with Java as its main programming language. The application also uses the PHP Framework and MySQL databases with servers that are online. With this application, prospective Jeti can Kokoro about accurate travel related from the time, route, village TARIFF i.e. make a reservation and payment can be made in a grip anytime and anywhere.